Literasi Digital: Penelitian Tindakan Kelas Bagi Siswa SMK - Juita Haryani (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this research is to find out students' digital literacy abilities and find out what actions are appropriate to take in order to increase students' digital literacy. Methodology: This study used a class action research method with the Jhon Elliot research model design. This research model consists of a cycle in which there are several stages, namely design, implementation (action), observation, and reflection Main Findings: The findings of this research is that students' digital literacy skills in the first cycle with conventional learning models are dominant in the bad category. Then in the second cycle by using a project-based learning model and utilizing technology directly it is known that students' digital literacy has increased where it is more dominant in the good category. So that the actions that can be taken by educators to improve students' digital literacy are by using a project-based learning model that is supported by sufficient learning media. Novelty/Originality of this study: The novelty of this research is that it was conducted at the vocational high school level, then focused on appropriate classroom actions to increase students' digital literacy in Indonesian language subjects.